Introduction to linear Algebra - Tay , Choo Chuan; Sakidin, Hamzah; Jamaludin, Irma Wani; Abdul Razak, Norazlina; Anwar Apandi, Nur Ilyana (Penerbit Universiti, UTeM, 2010)
One of the most challenging aspects of mathematics learning is to give students suitable examples and exercises which can improve their understanding.